2006
DOI: 10.1002/mrd.20518
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor CREMτ and cAMP regulate promoter activity of the Na,K‐ATPase α4 isoform

Abstract: The Na,K-ATPase is an essential enzyme of the plasma membrane that plays a key role in numerous cell processes that depend on the transcellular gradients of Na(+) and K(+). Among the various isoforms of the catalytic subunit of the Na,K-ATPase, alpha4 exhibits the most limited pattern of expression, being restricted to male germ cells. Activity of alpha4 is essential for sperm function, and alpha4 is upregulated during spermatogenesis. The present study addressed the transcriptional control of the human Na,K-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 88 publications
3
13
0
Order By: Relevance
“…The conserved pattern in male germ-cell developmental stages in seminiferous tubules from α4 knockout mice suggests that the α4 isoform is not essential for the process of spermatogenesis, but rather that α4 is important for the differentiated sperm. This is supported by previous findings, showing that α4 is expressed after meiosis of the male germ cells and during late stages of spermatogenesis (7,11,22).…”
Section: Discussionsupporting
confidence: 91%
“…The conserved pattern in male germ-cell developmental stages in seminiferous tubules from α4 knockout mice suggests that the α4 isoform is not essential for the process of spermatogenesis, but rather that α4 is important for the differentiated sperm. This is supported by previous findings, showing that α4 is expressed after meiosis of the male germ cells and during late stages of spermatogenesis (7,11,22).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it appears that the ATP1a4 promoter does already drive low levels of GFP expression in spermatocytes. The ATP1a4 promoter driven expression of GFP at late stages of spermatogenesis is consistent with our previous observations, which showed that the proximal 5' untranslated region of the human Na,K-ATPase ATP1a4 promoter contains CRE binding elements that respond to the testis specific activator of transcription CREMτ [17], a transcription factor that is a master controller of post-meiotically activated genes of male germ cells [30]. Therefore, our current data support the notion that the ATP1a4 promoter forms part of the transcription regulatory machinery that is up-regulated after meiosis to serve important roles in the mature spermatozoa.…”
Section: Discussionsupporting
confidence: 91%
“…These sequences, identified as the proximal promoter regions of α4 (Atp1a4 promoter) have regulatory sites that drive the expression of the ATP1a4 gene [17,18]. In the present work, we have taken advantage of the endogenous Atp1a4 promoter to drive the expression of the Green Fluorescent Protein (GFP) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…The mouse spermatogonial stem cell line GC1-spg was chosen due to lack of an available human spermatogonial cell line. This cell line has been previously used to understand the transcriptional regulatory mechanism of the sperm-specific human ATP1A4 gene (Rodova M et al, 2006). We chose a somatic cell line and a germ cell line for our luciferase assays in order to explore cell type specific differences in the activities of the putative SLC9B1 promoters.…”
Section: Resultsmentioning
confidence: 99%